2012
DOI: 10.1096/fj.12-223305
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial thioredoxin reductase: an antibiotic mechanism targeting bacteria lacking glutathione

Abstract: Increasing antibiotic resistance makes the identification of new antibacterial principles an urgent task. The thioredoxin system including thioredoxin reductase (TrxR), thioredoxin (Trx), and NADPH plays critical roles in cellular DNA synthesis and defense against oxidative stress. Notably, TrxR is very different in structure and mechanism in mammals and bacteria. Ebselen [2-phenyl-1,2 benzisoselenazol-3(2H)-one], a well-known antioxidant and a substrate for mammalian TrxR and Trx, is rapidly bacteriocidal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
174
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(182 citation statements)
references
References 46 publications
6
174
0
2
Order By: Relevance
“…Downregulation or inhibition of Trx sensitized, whereas downregulation of TXNIP blunted the cell response to ADR. Of note, the important role of TrxR in prevention of oxidative cell injury has been previously documented (Andoh et al, 2002;Fang and Holmgren, 2006;Du et al, 2009;Carvalho et al, 2011;Lopert et al, 2012;Lu et al, 2013). Our results thus indicate that increasing Trx reducing activities is the major mechanism behind the antioxidative effect of AMPK.…”
Section: Ampk Attenuates Oxidative Cell Injurysupporting
confidence: 75%
“…Downregulation or inhibition of Trx sensitized, whereas downregulation of TXNIP blunted the cell response to ADR. Of note, the important role of TrxR in prevention of oxidative cell injury has been previously documented (Andoh et al, 2002;Fang and Holmgren, 2006;Du et al, 2009;Carvalho et al, 2011;Lopert et al, 2012;Lu et al, 2013). Our results thus indicate that increasing Trx reducing activities is the major mechanism behind the antioxidative effect of AMPK.…”
Section: Ampk Attenuates Oxidative Cell Injurysupporting
confidence: 75%
“…Involvement of reactive-oxygen species in the bactericidal effect of antibiotics was proposed (25)(26)(27). On the other hand, it was reported that thioredoxin plays a protective role against oxidative stress in bacteria (28)(29)(30)(31)(32). In S. aureus COL, there are three putative thioredoxins, SACOL1794 (Trx), SACOL0875, and SACOL1155.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, class C compounds were chemically interesting, as all seven members of this class had a substructure of 2-phenyl-2,3-dihydro-1,2-benzothiazol-3-one; this compound substructure is also called ebsulfur. 25,26 Using compound 1 as a positive control hDAAO inhibitor, we characterized, in a panel of biochemical assays, properties of commercially available compounds with the class C substructure. Although these compounds were not the exact compounds emerging from the HTS, because of their chemical similarity, they are furthered referred to as "class C compounds."…”
Section: Biochemical Characterization Of Class C Compound Hdaao Inhibmentioning
confidence: 99%